Monitoring animal populations and their habitats : a practitioner's guide - McComb, Brenda C. (CRC Press, 2010)
"In the face of so many unprecedented changes in our environment, the pressure is on scientists to lead the way toward a more sustainable future. Written by a team of ecologists, Monitoring Animal Populations and Their Habitats: A Practitioner's Guide provides a framework that natural resource managers and researchers can use to design monitoring programs that will benefit future generations by distilling the information needed to make informed decisions. In addition, this text is valuable for undergraduate- and graduate-level courses that are focused on monitoring animal populations. With the aid of more than 90 illustrations and a four-page color insert, this book offers practical guidance for the entire monitoring process, from incorporating stakeholder input and data collection, to data management, analysis, and reporting. It establishes the basis for why, what, how, where, and when monitoring should be conducted; describes how to analyze and interpret the data; explains how to budget for monitoring efforts; and discusses how to assemble reports of use in decision-making. The book takes a multi-scaled and multi-taxa approach, focusing on monitoring vertebrate populations and upland habitats, but the recommendations and suggestions presented are applicable to a variety of monitoring programs. Lastly, the book explores the future of monitoring techniques, enabling researchers to better plan for the future of wildlife populations and their habitats. It furthers the goal of achieving a world in which biodiversity is allowed to evolve and flourish in the face of such uncertainties as climate change, invasive species proliferation, land use expansion, and population growth."--Publisher's description